UNATTENDED VERSUS ATTENDED BP MEASUREMENT: RELATIONSHIP WITH 24 HOURS BLOOD PRESSURE VALUES. (April 2021) - Salvetti, Massimo; Paini, Anna; Bertacchini, Fabio; Aggiusti, Carlo; Stassaldi, Debora; Capellini, Sara; Saccà, Giovanni; Arnoldi, Chiara; De Ciuceis, Carolina; Rizzoni, Damiano; Bertini, M.; Gatta, Roberto; et al.
Abstract : Objective: It has been suggested that measurement of "unattended" or "automated oscillatory" blood pressure(BP) values (AOBP) may provide advantages over conventional BP measurement. More data are needed on the relationship between BP values measured by the conventional approach, by AOBP and values obtained by 24 hours BP monitoring (ABPM). Design and method: In 607 consecutive patients attending the outpatient clinic at an ESH Excellence Centre, BP values were measured by the physician with an automated oscillometric device (Omron HEM 9000Ai, mean of 3 measurements), after 5 minutes of rest. After the measurement of BP by the physician, the patient was left alone in the room, and the device was programmed to automatically perform 3 BP measurements after 5 minutes. ABPM was performed in all subjects. Results: Mean age was 60 ± 13 yrs, 53% females, BMI 26 ± 4, 77 % with a previous diagnosis of hypertension (58 % treated). Unattended systolic BP (SBP) (126.4 ± 14.5) was lower as compared to attended SBP (132.7 ± 15.9mmHg) and to 24 hours daytime BP (129.4 ± 14.5 mmHg). Attended and unattended SBP were similarly correlated to daytime BP (r = 0.649, R = 0.669, P < 0.000, p for the comparison between r ns). The differences (d) between SBP values obtained using the three techniques were 6.3 ± 7.7 mmHg (attended-unattended), 3.5 ± 12.2 mmHg (attended-daytime BP) and – 2.8 ± 11.0 (unattended-daytime). Conclusions: Our findings indicate that "unattended BP" measurement provides values significantly lower as compared to measurements obtained in the presence of the physician and also to 24 hours daytime BP. In our population BP values obtained by the unattended approach are similar to 24 hours daytime BP values. However 24 hours daytime BP was similarly correlated to both attended and unattended BP